Las Tecnologías de la Información y Comunicación y su Influencia en el Comportamiento de las Niñas y Niños de la Escuela “Manuel José Aguirre” - AGURTO TORRES, MARÍA FERNANDA (2016)
This research was conducted at "Manuel José Aguirre" school of the city of Loja with students in fifth, sixth and seventh year of basic education, with the firm intention of knowing how technologies influence the behavior of children in which it was known what kind of content use and manage students daily with technologies such as the Internet, cellular and television, thereby determining their influence and understanding the reasons why their behavior has been modified and has been manifested through the dissatisfaction and concern by teachers, parents and classmates, allowing at the same time identify the importance of the actions of the social worker in this issue. Additionally, the development of this research, allowed to fulfill the objectives, referring first to the general objective, aimed to guide the proper use of technologies for the behavior of children look improved, and carried out by development of the three specific objectives in which the theoretical and scientific basis of the categories that support the object of study, among which are established: the influence from the social point of view, technologies such as television, the internet and cell, behavior from the psychological point of view, the legal framework with the Constitution and the Code of Children and Adolescents, and Social Worker intervention against the object of study; whereas the use of survey allowed diagnose the causes and effects that the use of technology in the behavior of children, setting off in compliance with the third specific objective in designing a proposal for social action aimed at guiding through training and awareness, the proper management of the aforementioned technologies for the students' behavior improved look. To carry out the execution of this research, field work was carried out, through which surveys of students, parents and teachers were applied, evidencing the existence of the negative influence of technologies like the Internet, cell and television on children, the little appropriate content to which they are exposed, adding to this ignorance and poor parental control at home and proper guidance of teachers in the school, which has served as a factor determinant in student behavior. 5 It was found that most children are active users of technologies, especially the Internet, television, phone and computer, used for entertainment with video games, TV shows and YouTube videos, of which receive negative influence so harmful that happen to be most content in these shows and that, because of the minor and limited knowledge that parents and teachers remain on these issues, given as a result that student behavior is seen as a problem for teachers when they are in the classroom and for parents when they are at home. In this situation, it was considered necessary to design a proposal that would allow the educational community understanding and awareness about the importance of dealing with today's technologies, and how the family and the school must function as promoters of welfare emotional and social the boy and girl. The research was developed based on a methodology of quantitative and qualitative established with the scientific method and other auxiliary methods as deductive , inductive, the statistical method and descriptive , which allowed to fulfill the objectives and respond to problem under study . Keywords: influence, technology, behavior, social workers, students, parents, teachers.